2021
DOI: 10.1159/000519067
|View full text |Cite
|
Sign up to set email alerts
|

Exceptionally Steep Brain-Body Evolutionary Allometry Underlies the Unique Encephalization of Osteoglossiformes

Abstract: Brain-body static allometry, which is the relationship between brain size and body size within species, is thought to reflect developmental and genetic constraints. Existing evidence suggests that the evolution of large brain size without accompanying changes in body size (that is, encephalization) may occur when this constraint is relaxed. Teleost fish species are generally characterized by having close-fitting brain-body static allometries, leading to strong allometric constraints and small relative brain si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 100 publications
0
10
0
Order By: Relevance
“…This is of particular interest, because fish brains continue to show high levels of neurogenesis also in adulthood, in stark contrast to the very limited cellular development and regeneration of adult avian and mammalian brains (Zupanc & Horschke, 1995; Ganz & Brand, 2016). By extending the potential timeframe for brain growth, this may alter the costs and benefits of large brains in fishes (Tsuboi, 2021), despite the allometric relationships between body mass and brain mass in adults being similar for all vertebrate classes (Tsuboi et al, 2018). After initial examination of the data, we thus selected six ecological/phenotypic traits relevant to the above hypotheses, and devised three principal models to correlate these traits with brain weight, the most widely available measure of brain size, in a phylogenetically controlled way.…”
Section: Introductionmentioning
confidence: 99%
“…This is of particular interest, because fish brains continue to show high levels of neurogenesis also in adulthood, in stark contrast to the very limited cellular development and regeneration of adult avian and mammalian brains (Zupanc & Horschke, 1995; Ganz & Brand, 2016). By extending the potential timeframe for brain growth, this may alter the costs and benefits of large brains in fishes (Tsuboi, 2021), despite the allometric relationships between body mass and brain mass in adults being similar for all vertebrate classes (Tsuboi et al, 2018). After initial examination of the data, we thus selected six ecological/phenotypic traits relevant to the above hypotheses, and devised three principal models to correlate these traits with brain weight, the most widely available measure of brain size, in a phylogenetically controlled way.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found a steeper brain–body allometric relationship for osteoglossiforms compared to other actinopterygians, but not for seven other focal ray-finned fish orders, which may, in part, be driven by the highly speciose mormyroids ( Tsuboi, 2021 ). To determine if the evolution of an electrosensory system is associated with extreme encephalization or shifts in brain–body allometric relationships, we combined our data with published brain and body mass data across ray-finned fishes ( Tsuboi, 2021 ; Tsuboi et al, 2018 ), which resulted in a combined dataset of 870 species across 46 orders, with phylogenetic data from a previously assembled time-calibrated phylogeny ( Rabosky et al, 2018 ). We used Bayesian reversible-jump bivariate multiregime Ornstein–Uhlenbeck modeling (OUrjMCMC; Uyeda et al, 2017 ) to identify shifts in both y-intercept and slope of brain–body allometric relationships.…”
Section: Resultsmentioning
confidence: 98%
“…Indeed, when we allow only intercept to vary between grades while assuming parallel slopes, we no longer detect any reliable grade shifts within actinopterygians. Even when allowing slope to vary, two of our identified shifts were undetectable when assuming the brain–body allometry is constant within orders despite analyzing much of the same data ( Tsuboi, 2021 ).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations